The Effect of Peer Assessment through Twitter on Students’ Writing the Analytical Exposition Text Ability - Habiburrohman Habiburrohman; Eli Supartini; Paul Onsare Onchera (Journal of Language, Literature, and Educational Research, 2024)
Purpose of the study: This research is aimed to get empirical evidence on the effect of peer assessment through Twitter on students’ writing the analytical exposition text ability at eleventh-grade students of Senior High School 1 Dramaga Methodology:This research used the quantitative method and quasi-experimental design. The sample consisted of 60 eleventh-grade students from Senior High School 1 Dramaga, selected using purposive sampling. The samples were divided into two groups of 30 class XI social science 2 as the control class and class XI social science 3 as the experimental class. Then, the data were collected by using a writing test in the form of a pre-and post-test. Main Findings: The result shows that the mean score of the post-test in the experimental class is 78.133 with 17.633 as the gained mean score while the mean score of the post-test in the control class is 70.167 with 8.167 as the gained mean score. Besides, the result shows that sig (2 tailed) is 0.000. Then the tvalue of the post-test (4.396) is higher than ttable (2.301) meaning Ha is accepted and H0 is rejected. Novelty/Originality of this study:This research offers novelty by exploring in depth the influence of learning methods based on Islamic values ​​on language politeness in class VIII student discussions at SMPIT Ash Shiddiqiyyah Tangsel.